Consumo e construções midiáticas: corpos diferentes no futebol - Franco, Ednaldo Edilei (2012)
This investigation aims at discussing the consumption related to the ―world of ball‖ and to the media constructions from the soccer culture perspective in the national collective thought. The theme of the research is the media construction of the ―different body‖ characterized by being different from the known model of the player and the analysis is focused on the media strategies for the construction of this ―dissonant body‖ representations in the interface between communication and consumption. The analysis was restricted by the construction of Ronaldo Luíz Nazário de Lima s image in the media, considering two phases of his carrier: 1) in the beginning, when he is presented as a phenomenon and 2) in the moment right after his retirement, characterized by his physical decadence. In order to pursue these phases, the corpora include the news found in the press media from 1996 to 2011. The French Approach Discourse Analysis is the most important theoretical assumption chosen to investigate the strategies for media constructions. The studies on communication and consumption were also considered for a better comprehension of this media phenomenon in Brazilian society.